Suitability of a generic virus safety evaluation for monoclonal antibody investigational new drug applications. (9th June 2019) - Sipple, Patrick; Nguyen, Tung; Patel, Krina; Jaffe, Neil; Chen, Yan; Khetan, Anurag
Abstract: Biologics produced from CHO cell lines with endogenous virus DNA can produce retrovirus‐like particles in cell culture at high titers, and other adventitious viruses can find their way through raw materials into the process to make a product. Therefore, it is the industry standard to have controls to avoid introduction of viruses into the production process, to test for the presence of viral particles in unclarified cell culture, and to develop purification procedures to ensure that manufacturing processes are robust for viral clearance. Data have been accumulated over the past four decades on unit operations that can inactivate and clear adventitious virus and provide a high degree of assurance for patient safety. During clinical development, biological products are traditionally tested at process set points for viral clearance. However, the widespread implementation of platform production processes to produce highly similar IgG antibodies for many indications makes it possible to leverage historical data and knowledge from representative molecules to allow for better understanding and control of virus safety. More recently, individualized viral clearance studies are becoming the rate‐limiting step in getting new antibody molecules to clinic, particularly in Phase 0 and eIND situations. Here, we explore considerations for application of a generic platform virus clearance strategy that can be applied for relevant investigational antibodies within defined operational parameters in order to increase speed to the clinic and reduce validation costs while providing a better understanding and assurance of process virus safety.